El Excentrico, 1958-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
Janurary 5, 1958 [5 de enero de 1958]. Ano 8, No. 9. Cover contains a photo of El Excentrico's photographers Gloria Porras, Della Maes, and Dolores Coca, using a process camera to take a picture of a baby doll, which they call the "newlyborn 1958." The headline reads, "Gloria Prras, Della Maes and Dolores Coca run newlyborn 1958 thru the complexities of Excentrico's Process Camera."